The Influence of Dynamic Capabilities on Organisational Performance: An Empirical Study on Qatar#x2019;s Ministry of Finance (Global Journal of Management and Business Research, 2020)
This research aimed to explain the influence of dynamic capabilities on organisational performance in Qatar's ministry of finance. The research population consisted of top management in which included (managers, vice manager, Department Manager, and Vice Department Manager) in Qatar's ministry of finance. A complete census method used to collect data based on the small size of the population. Structural equation modelling (SEM) used to analyse data and test hypotheses. The research results indicated that there is a statistically significant influence of dynamic capabilities with their dimensions in which were (sensing, seizing, and reconfiguration) on organisational performance.
Keywords: dynamic capabilities; organisational performance; ministry of finance; qatar